UNDERSTANDING KENYA’S ELECTORAL MANAGEMENT ARCHITECTURAL CONTEXT: SURVIVING BOTH THE STATE AND A VOLATILE REGION - Thomas Jouma (Journal of Diplomacy and International Studies, 2020)
The article is an attempt to understand Kenya’s electoral management architectural context asks fundamental questions; does elections management architectural context have the ability to survive a state or group of states? How does election management architecture help states function in volatile regions? While answering these, the study asserts; in a deepening regionalism, the security effects of one state extend threats to other communities of states around it/her. In a critical view from the prism of the International Relations (IR) lens, the survival of one state has a spiral survival effect on the other states in such a locality. This causes states to have joint and various effects relationships. The nature of regional security among neighboring states faces paradigmatic limitations common to their adjacency. Security in the era of regionalization is symbiotic thus poor electoral management naturally has an impact on the existing peace and security in a regional network of states. This study discussed Kenya’s electoral management architecture from the constitutional edicts point of view. This encompassed strengths and weaknesses observed and highlight some supportive Acts of law found necessary to the study. It moved further to elaborate on the electoral management architecture context found relevant to the study. Using relevant themes, the study analyzes the region in light of the questions posed and written literature, the research justifiably concludes that indeed EM architectural context has a necessary role in volatile regions.